2002
DOI: 10.1017/s0967026201003493
|View full text |Cite
|
Sign up to set email alerts
|

Pyramimonas australis sp. nov. (Prasinophyceae, Chlorophyta) from Antarctica: fine structure and molecular phylogeny

Abstract: An undescribed marine Pyramimonas, P. australis Andreoli et Moro, sp. nov., forming a bloom in a hole of Terra Nova Bay (Ross Sea, Antarctica) sea ice, was collected, but could not be cultured. Consequently, the description of this new species is based on light and electron microscope observations on samples that were fixed or stored at -80 degreesC, and its phylogenetic position inferred from nuclear-encoded small-subunit ribosomal DNA (SSU rDNA) and chloroplast-encoded rbcL gene sequences. This is the third … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 40 publications
5
21
0
2
Order By: Relevance
“…The Pyramimonas cyst formation began with the motile single‐celled quadriflagellate (van den Hoff et al. 1989; Daugbjerg 2000; Moro et al. 2002), but cysts could also be the product of the multilobed stage observed in culture, because we saw on one occasion a multilobed form containing a thickened internal cyst‐like wall structure, a single nucleus and a diffuse mass of DNA.…”
Section: Discussionmentioning
confidence: 81%
“…The Pyramimonas cyst formation began with the motile single‐celled quadriflagellate (van den Hoff et al. 1989; Daugbjerg 2000; Moro et al. 2002), but cysts could also be the product of the multilobed stage observed in culture, because we saw on one occasion a multilobed form containing a thickened internal cyst‐like wall structure, a single nucleus and a diffuse mass of DNA.…”
Section: Discussionmentioning
confidence: 81%
“…The green alga Pyramimonas was also abundant in the north-eastern shelf of Kangaroo Island. It is a highly diverse genus which has been frequently reported in polar waters (Balzano et al, 2012;Bell and Laybourn-Parry, 2003;Moro et al, 2002) but was also previously observed in south-eastern Australia (McFadden et al, 1986) and in the Gulf Saint Vincent .…”
Section: Large Phytoplanktonmentioning
confidence: 58%
“…To amplify 18S rDNA, the conditions were as follows: initial denaturation at 948C for 3 min followed by 35 cycles of 948C for 30 s, 508C for 30 s, 728C for 1-2 min and a final extension at 728C for 10 min. For rbcL, the conditions were from Moro et al (2002). PCR products were purified and sequenced at Macrogen Japan (Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%